2016
DOI: 10.1073/pnas.1607996113
|View full text |Cite
|
Sign up to set email alerts
|

Resource scarcity drives lethal aggression among prehistoric hunter-gatherers in central California

Abstract: The origin of human violence and warfare is controversial, and some scholars contend that intergroup conflict was rare until the emergence of sedentary foraging and complex sociopolitical organization, whereas others assert that violence was common and of considerable antiquity among small-scale societies. Here we consider two alternative explanations for the evolution of human violence: (i) individuals resort to violence when benefits outweigh potential costs, which is likely in resource poor environments, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 31 publications
(33 reference statements)
6
63
0
1
Order By: Relevance
“…In particular, our results are consistent with recent findings showing that reduced environmental productivity is a strong predictor of lethal aggression among prehistoric groups in Central California [24]. …”
Section: Discussionsupporting
confidence: 93%
“…In particular, our results are consistent with recent findings showing that reduced environmental productivity is a strong predictor of lethal aggression among prehistoric groups in Central California [24]. …”
Section: Discussionsupporting
confidence: 93%
“…The important edited volume by Allen and Jones (2014) provides archaeological surveys and case studies of intense warfare among North American and Australian hunter-gatherers in the absence of contact with agriculturalists (see also Lambert 2002 for a classic survey of North America). Research on Californian hunter-gatherers is of particular significance because of the tremendous amount of skeletal evidence of lethal trauma in areas far from agricultural centers (Allen et al 2016). And in Australia, archaeological evidence as well as historical and ethnohistoric evidence document frequent warfare from ecologically rich drainages such as the Murray River as well as resource-poor desert areas as well (Allen 2014b).…”
Section: Archaeology Agriculture and Warfarementioning
confidence: 99%
“…In a sample of 19 hunter‐gatherer societies, Kelly found a positive correlation between the occurrence of war and population pressure, as measured by how much food is available per person. Moreover, Allen et al found that lethal violence was significantly and better predicted by resource scarcity than by socio‐political complexity (a proxy of the extent to which leaders can coerce their subordinates to go to war), using archeological data on hunter‐gatherer societies in Central California. Finally, it has been proposed that lethal aggression in humans became more frequent in the last 15,000–8,000 year BP (but see Reference ), when population density increased, groups settled down near resource‐rich locations (e.g., river estuaries) and started monopolizing those locations …”
Section: Six Debated Points On the Role Of Warfare In Human Evolutionmentioning
confidence: 99%